Deteksi Virus Terbawa Umbi Benih pada Bawang Merah Kultivar Biru Bantul - Nurviani Nurviani; Sri Sulandari; Susamto Somowiyarjo; Siti Subandiyah (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2016)
Virus infection on shallots may cause mosaic of leaves and plant dwarf. It is very important to know the identity of the virus as a requirement in determining viral disease management strategy. The research is subjected to identify seed- transmitted viruses from shallot bulbs. Detection of virus from bulb was conducted by growing on test, followed by mechanical inoculation on shallot cultivar Biru Bantul, Chenopodium amaranticolor, and Nicotiana tabacum and morphological observation of virus particle by electron microscope. About 2 weeks after inoculation symptoms was observed, i.e. mosaic and dwarf on shallot cultivar Biru Bantul, local necrotic on C. amaranticolor, but symptomless on N. tabacum. Filamentous particles of 650 nm and 800 nm in length was observed under electron microscope from plants with mosaic and dwarfing symptom, respectively. This indicated the presence of 2 different seed-transmitted viruses on infected shallots. Two species of shallot viruses, i.e. Shallot latent carlavirus (SLV) and Onion yellow dwarf potyvirus (OYDV) was most likely the main seedborne viruses on shallot bulb. Identification based on nucleic acid and protein sequence analysis is necessary for further confirmation